"First STEP" or Nature Deserves a Second Chance! Systematic Literature Review and Meta-analysis - Bashar Aldeiri; Riccardo Coletta; Antonino Morabito (EL-Med-Pub, 2018)
Aim: Surgical management of short bowel syndrome (SBS) in children is challenging. Recently, more authors are advocating for the neonatal serial transverse enteroplasty procedure (STEP) in SBS quoting the term "primary STEP" or "first STEP." This review sought to identify the current published indications for neonatal STEP and to analyze their subsequent outcomes. Methods: We performed an OVID MEDLINE/ EMBASE search using the keywords: (Bowel, enteroplasty, intestinal lengthening, STEP, and short bowel) limited to children since the introduction of STEP in 2003 prospero systematic review registration number (CRD42017076955). Results: Thirteen papers matched our search criteria, and accurate data were available from 10 papers. A total of 26 cases had a STEP procedure at a median age of 2.5 days. The primary diagnosis was Jejunal atresia (62%), gastroschisis (19%), gastroschisis with atresia (15%), and midgut volvulus (4%). Almost a third (7/23) of the cases did not meet the anatomical definition of SBS and had a pre STEP residual small bowel (SB) length of ≥50 cm. Only 6 cases (26%) achieved enteral autonomy after the "first STEP," interestingly in half the pre STEP SB length was ≥90 cm, 13 (56%) required a second STEP, 9 (40%) are still parenteral nutrition dependant, 4 more cases achieved enteral autonomy following a second STEP, 3 infants died, and one required SB transplantation. Significant post-operative complications were reported in four cases, and bowel redilatation occurred in almost all true SBS cases. Conclusion: Redilatation following "first STEP" is very common, may influence the ability to achieve enteral autonomy and generally necessitates further surgical intervention. The limited current evidence does not support the widespread use of STEP in the neonatal period. STEP can be a method of mucosal-sparing tailoring procedure; however, its outcomes in primary bowel lengthening in the neonatal period are yet to be established, and further studies are required before it is widely adopted.